Multiparentality and the legal effects of its recognition (Research, Society and Development, 2021)
This study deals with Multiparenthood and the legal effects of its recognition and presents as a guiding question: “What are the legal effects arising from the recognition of multiparenting?”. The research has the scope of understanding the legal repercussions arising from the referred institute and has as specific objectives: to discuss the affiliation in Brazilian law, to point out the principles that govern family law, to analyze the general provisions that deal with multiparenting, as well as to investigate its legal repercussions. Bibliographic research was used, with research in books and current legislation, in addition to articles searched in the main databases, such as Google Academic and Scielo, with the words: multiparenthood, paternity and legal effects as descriptors. The main authors used were Cristiano Chaves de Farias and Nelson Rosenvald, Maria Berenice Dias, Conrado Paulino da Rosa and Flávio Tartuce. Documentary research was also used, with the analysis of judgments that allowed a detailed understanding of the institute under discussion, given that the General Repercussion Thesis No. 622, signed by the Federal Supreme Court, made it clear that there is no hierarchy between the biological paternity and socio-affective and that both can exist, simultaneously, generating their own legal effects, leaving it clear that the referred thesis generates several legal repercussions, among which the right to name, alimony, custody/visit and inheritance rights can be cited. Finally, there are several consequences arising from the understanding of the Brazilian courts, it is worth mentioning that the doctrine has played a prominent role in the interpretation of such legal effects, since this is a recent issue and there is no specific rule to specifically regulate each case.